Sudan’s Mpox surveillance system during the 2022 pandemic: a retrospective evaluation - Izzoddeen, Ahmad; Elbadri, Omer; Musa, Magam; Dafaalla, Alaa Hamed; Abasher, Mazza; Magbol, Mustafa; Elhasan, Muntasir M. O.; Abdalla, Mohamed Nageeb (Frontiers in Public Health, 2025)
BackgroundMpox (formerly monkeypox) is a zoonotic disease caused by the Mpox virus. Although the disease is endemic in several Central and West African countries, it has recently emerged in Europe and the United States and was declared a public health event of international concern. This study aimed to evaluate Mpox surveillance in Sudan and provide insights for better epidemic preparedness.MethodsMpox surveillance was evaluated based on Centers for Disease Control and Prevention guidelines. The targeted attributes were flexibility, sensitivity, usefulness, representativeness, timeliness, and data quality (data completeness and adequacy of variables). To evaluate the qualitative attributes (flexibility, usefulness, and representativeness), interviews were conducted with key informants, supported by records and reports review. The national surveillance line-list was obtained for evaluation of the quantitative attributes: timeliness, data quality, and sensitivity.ResultsThe surveillance system was flexible enough to integrate Mpox within a short time. A technical committee was formulated, and a preparedness and response plan developed. The case definition was adapted and reporting activated through different surveillance types. Surveillance was useful in detecting Mpox, generating epidemiologic indicators, and guiding preparedness and response interventions. The system showed representativeness geographically and through multiple reporting sources. The case definition was broadly sensitive as it detected Mpox cases and other dermatological conditions, with proven detection capacity by different surveillance types. The line-list lacked important data on medical history and exposure. The timeliness of reporting was good; however, the testing capacity was limited.ConclusionThe surveillance system demonstrated high flexibility in rapidly integrating Mpox, with sensitivity in detecting cases and representative reporting sources. It was useful in detecting Mpox, generating epidemiologic indicators, and informing actions. Improvement in data quality and completeness is required for in-depth analysis. Rapid response teams’ training and sustainable financing for their operations are highly recommended and crucial for timely investigation, quality data, and specimen collection. Expanding molecular-testing capacity to regional laboratories and strengthening specimen-transport networks are critical, together with shifting to a One Health approach.